The epidemiology of life‐threatening complications associated with reproductive process in public hospitals in Argentina. Issue 13 (13th August 2013) - Karolinski, A; Mercer, R; Micone, P; Ocampo, C; Mazzoni, A; Fontana, O; Messina, A; Winograd, R; Frers, MC; Nassif, JC; Elordi, HC; Lapidus, A; et al.
Abstract : Objective: To analyse life‐threatening obstetric complications that occurred in public hospitals in Argentina. Design: Multicentre collaborative cross‐sectional study. Setting: Twenty‐five hospitals included in the Perinatal Network of Buenos Aires Metropolitan Area. Population: Women giving birth in participating hospitals during a 1‐year period. Methods: All cases of severe maternal morbidity (SMM) and maternal mortality (MM) during pregnancy (including miscarriage and induced abortion), labour and puerperium were included. Data were collected prospectively. Main outcome measures: Identification criteria, main causes and incidence of SMM; case‐fatality rates, morbidity–mortality index and effective intervention's use rate. Results: A total of 552 women with life‐threatening conditions were identified: 518 with SMM, 34 with MM. Identification criteria for SMM were case‐management (48.9%), organ dysfunction (15.2%) and mixed criteria (35.9%). Incidence of SMM was 0.8% (95% confidence interval [95% CI] 0.73–0.87%) and hospital maternal death ratio was 52.3 per 100 000 live births (95% CI 35.5–69.1). Main causes of MM were abortion complications and puerperal sepsis; main causes of SMM were postpartum haemorrhage and hypertension. Overall case‐fatality rate was 6.2% (95% CI 4.4–8.6): the highest due to sepsis (14.8%) and abortion complications (13.3%). Morbidity‐mortality index was 15:1 (95% CI 7.5–30.8). Use rate of known effective interventions to prevent or treat main causes of MM and SMM was 52.3% (95% CI 46.9–57.7). Conclusions: This study describes the importance of life‐threatening obstetric complications that took place in public hospitals with comprehensive obstetric care and the low utilisation of known effective interventions that may decrease rates of SMM and MM. It also provides arguments that justify the need to develop a surveillance system for SMM.